Quality of Ethanol Produced from Aren Sap as Influenced by Fermentation and Tapping Time - Desi Narahawarin; Herman Siruru; Jimmy Titarsole; Lydia Riekie Parera (Mandalika Institute, 2026)
Aren sap (Arenga pinnata) has considerable potential as a feedstock for bioethanol production due to its high sugar content, which can be directly fermented. Its sugar concentration is influenced by photosynthetic activity; therefore, tapping time is presumed to affect the quality of the resulting bioethanol. This study aimed to evaluate the effects of tapping time (morning and afternoon) and fermentation period (2, 4, 6, and 8 days) on the quality of ethanol produced from aren sap. The research was conducted from March to April 2026 at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Pattimura, Ambon, using a factorial Completely Randomized Design (CRD). The results showed that afternoon tapping produced a higher sugar content (69.71%) than morning tapping (59.47%). In addition, an 8-day fermentation period yielded the highest ethanol quality, as indicated by its calorific value (131.81 kcal/kg), density (0.9381 g/mL), and specific gravity (0.9649 g/mL). It can be concluded that the combination of afternoon tapping and an 8-day fermentation period produced the highest-quality bioethanol. However, the resulting ethanol did not yet meet the requirements of SNI 7390:2012, indicating that further optimization of the distillation process is still necessary.